Nuclear Weapons From the Lens of the UN Charter - Syifa Syarifa (Dinasti Research, 2024)
Nuclear weapons have been a longstanding topic of debate in international law, as their presence brings up concerns about their legality and morality in relation to global peace and security, which are core principles of the United Nations (UN). This article analyses the provisions related to the possession, use, and threat of use of nuclear weapons under the UN Charter. Employing a qualitative approach and normative method, this article examines relevant legal documents and scholarly literature. The analysis shows that while the UN Charter does not directly regulate nuclear weapons, its principles have laid the foundation of the Non-Proliferation Treaty (NPT) and the Treaty on the Prohibition of Nuclear Weapons (TPNW). The possession of nuclear weapons is legally permitted for certain states under the NPT, provided they make sincere efforts toward achieving complete disarmament. Additionally, the use and threat of use of nuclear weapons must comply with the principles of international humanitarian law and customary law, which inherently cannot be fulfilled by nuclear weapons due to their nature.